Media Promosi Meta Ads Tinjauan Ekonomi Syariah: Studi pada Usaha Juragan Bubur Bengkulu - Deva Amalia Fitra; Andang Sunarto; Andi Harpepen (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this research is to examine promotional media using paid advertisements on Meta Ads as a promotional medium for Juragan Bubur business from the perspective of Islamic economics. To test this, the researcher employs a qualitative method with data collection techniques including interviews and documentation. The data analysis technique involves primary data sources through observation and interviews. From the research findings and discussions, it was discovered that the advertisement transactions on Meta Ads conducted by the Juragan Bubur Bengkulu business comply with the provisions outlined in Islamic economics. This is based on the fulfillment of requirements related to Ijab Kabul (offer and acceptance), subjects, wages, and objects.